Sagot :
Given:
[tex] \: \: \: \: \: \: \: \: \: \: \large \tt \frac{ {x}^{2} - \: 2x \: - \: 7 }{ {x}^{2} \: - \: 9 } = \frac{3x \: + \: 1}{ {x}^{2} \: - \: 9 \: } [/tex]
[tex] \: \: \: \: [/tex]
Solution:
Solving to the equation problem.
[tex] \: \: \: \: \: \: \: \: \: \: \large \tt \frac{ {x}^{2} - \: 2x \: - \: 7 }{ {x}^{2} \: - \: 9 } = \frac{3x \: + \: 1}{ {x}^{2} \: - \: 9 \: } [/tex]
[tex] \: \: \: \: \: \: \: \: \tt {x}^{2} - 2x - 7 = 3x + 1[/tex]
[tex] \: \: \: \: \: \: \tt {x}^{2} - 2x - 7 - 3x - 1 = 0[/tex]
[tex] \: \: \: \: \: \: \: \: \: \: \: \: \: \tt {x}^{2} - 5x - 8 = 0[/tex]
[tex] \large \tt x = \frac{ - ( - 5)± \sqrt{( - 5)^{2} - \: 4 \: \times \: 1 \times \: ( - 8) } }{2 \times 1} [/tex]
[tex] \: \: \: \: \: \: \: \: \: \: \: \: \large \tt x = \frac{5 ± \sqrt{25 \: + \: 32 \: } }{2} [/tex]
[tex] \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \large \tt x = \frac{5 ± \sqrt{57\: } }{2} [/tex]
[tex] \: \: \large \tt x = \frac{5 \: + \: \sqrt{57\: } }{2} \: \sf \: \small or \: \large \tt x = \frac{5 \: - \: \sqrt{57 \: } }{2} [/tex]
[tex] \: \: \: \: [/tex]
Answer:
Therefore, the solution of set to the equation is
- [tex] \boxed{ \blue{ \tt{ \frac{5 ± \sqrt{ 57 \: \: } }{2} }}}[/tex]
[tex] \: \: \: \: [/tex]